Downstream Oligonucleotides Strongly Enhance the Affinity of GMP to RNA Primer–Template Complexes - Tam, Chun Pong (J Am Chem Soc, 2017)
[Image: see text] Origins of life hypotheses often invoke a transitional phase of nonenzymatic template-directed RNA replication prior to the emergence of ribozyme-catalyzed copying of genetic information. Here, using NMR and ITC, we interrogate the binding affinity of guanosine 5′-monophosphate (GMP) for primer–template complexes when either another GMP, or a helper oligonucleotide, can bind downstream. Binding of GMP to a primer–template complex cannot be significantly enhanced by the possibility of downstream monomer binding, because the affinity of the downstream monomer is weaker than that of the first monomer. Strikingly, GMP binding affinity can be enhanced by ca. 2 orders of magnitude when a helper oligonucleotide is stably bound downstream of the monomer binding site. We compare these thermodynamic parameters to those previously reported for T7 RNA polymerase-mediated replication to help address questions of binding affinity in related nonenzymatic processes.